An intensive exercise-based training program reduces prefrontal activity during usual walking in patients with Parkinson's disease. (2022) - Hoang, I.; Ranchet, M.; Cheminon, M.; Derollepot, R.; Devos, H.; Perrey, S.; Luauté, J.; Danaila, T.; Paire-Ficout, L.
Highlights: Patients with Parkinson's disease have increased prefrontal activity during usual walking. After SIROCCO training, prefrontal activity decreased and gait performance improved in patients. An intensive exercise-based training program increased automaticity of gait in patients with PD. Findings highlight the potential of neuroplasticity in PD after exercise. Abstract: Introduction: Parkinson's disease (PD) leads to a progressive loss of locomotor automaticity. Consequently, PD patients rely more on executive resources for the control of gait, resulting in increased prefrontal activity while walking. Exercise-based training programs may improve automaticity of walking and reduce prefrontal activity in this population. This study aimed to assess the effect of an intensive multidisciplinary exercise-based training program on prefrontal activity and gait performance during usual walking in PD patients. Method: Fourteen patients (mean age: 67 ± 9; disease duration: 6 ± 5 years; Hoehn and Yahr score: 1.9 ± 0.6) were included in this study. They were assessed in ON stage at three different times at 5-week intervals: two times before the training program (T0 and T1) and once after the training program (T2). Gait performance (stride time, speed, stride length, cadence, and their respective coefficient of variation) and cortical activity in the dorsolateral prefrontal cortex (DLPFC) using functional near infrared spectroscopy (fNIRS) were measured during usual walking. Results: Patients had reduced cortical activity of the DLPFC at T2 compared to T1 (p = 0.003). Patients had shorter stride time at T2 compared to T1 (p = 0.025) and tended to have longer stride length at T2 than at T1 (p = 0.056). Conclusion: The training program led to positive effects on prefrontal activity and gait performance. Reduced prefrontal activity during usual walking after training program suggests that patients may have a greater reserve capacity to face more challenging walking conditions. Further studies will investigate the effect of this training on cortical activity during dual-task walking..